Eksploratif Sains Anak Usia Dini melalui Pembuatan Ice Cream Sederhana - Chasanah, Lailil Murro Nuril; Khotimah, Nurul (JOURNAL OF EDUCATION FOR ALL, 2024)
The purpose of this study is to determine the stages of implementing exploratory science for early childhood through the making of simple ice cream. The method used is literature review. The results of this study indicate that exploratory science for early childhood through the making of simple ice cream is one form of application of the concept of exploratory science. Through the stages of preparation, implementation, and closure, children are given the opportunity to explore natural phenomena related to changes in material state, cooling, and mixing of ingredients through the making of ice cream. In this process, they not only learn directly about basic scientific concepts such as physical changes and mixing of materials, but also train gross and fine motor skills and experience the results of their experiments. The overall activity enriches children's learning experiences and helps them understand the physical world in an interactive and enjoyable way.